Les parois des grottes : corps de l’image, cadre de la pensée des sociétés paléolithiques ? - Eric Robert (Images Re-Vues)
Body and frame, these two notions are closely declined within the art of Paleolithic caves in Europe. Paintings, engravings, sculptures, most often animals but also geometric signs take place on their walls. They offer both a “mineral body” (Pasqualini, 2019), hollowed out and shaped by water, and a framework for the physical inscription on these walls of the ideas and stories of these societies. Privileged context by Upper Paleolithic societies (40 – 15 ka BC) to inscribe representations, the walls of caves are also conducive to shaping games through the attention paid to natural reliefs, and their use to compose a part of the outline and the volume of the images, or underlining their place within the underground space. Wall, panel, gallery, room are all places that take on meaning in the close relationship to the image, and which give substance to an organized graphic expression, the oldest of human societies, where the artist/spectator dialectic already appears from remarkable complexity.